Advances in Smalltalk 14th International Smaltalk Conference, ISC 2006, Prague, Czech Republic, September 4-8, 2006, Revised Selected Papers - De Meuter, Wolfgang.; De Meuter, Wolfgang. (Programming and Software Engineering, 2007)
The 14th International Smalltalk Conference took place in the ?rst week of September 2006 in Prague, Czech Republic. This volume contains the pe- reviewed technical papers that were presented during the academic track of the conference. The International Smalltalk Conference evolvedout of the annual meeting of the European Smalltalk User Group (ESUG). This meeting usually lasts about a week and allows Smalltalk experts to discuss Smalltalk solutions and envir- ments. The meeting attracts a diverse audience consisting of Smalltalkers from industry as well as from academia. Thanks to the perpetual e?ort of people like St´ ephane Ducasse, Noury Bouraqadi, Serge Stinckwich and Roel Wuyts, over the years the ESUG meeting was provided with a separate academic research track during which researchers could present academic results about Smalltalk and its development tools. Unfortunately, no formal publication forum was - sociated with this track, which made it less attractive for authors to submit a paper. Starting with this edition of the conference, we hope this will change. An agreement was reached with Springer to publish a post-conference proceedings of this 14th edition. I think our community owes a big thank you to St´ ephane for this! Hopefully next year this agreement can evolve into a 15th edition of the conference with formally announced proceedings. This will certainly motivate more Smalltalk researchers to submit a paper! The conference accepted just over half of the submissions.